Unpacking the Linkages Between Structural Violence and the Climate Crisis - Arenas-García, Nahuel (Environmental ethics, 2024)
The connections between structural violence and the climate crisis have received scant attention in the literature, despite their significant implications. Structural violence is deeply entrenched in our social, cultural, and economic systems, to the extent ordinary individuals, engaged in legal and routine activities, can become indirect participants in harming others. The climate crisis is not only an expression of structural violence but also deepens structural violence, creating a vicious cycle through multi-directional and self-reinforcing linkages. To address violent outcomes and resolve the climate crisis, we need to shift power relations at the heart of our social and cultural arrangements. Taking a structural lens has the power to radically change how we tackle the problem of climate change. Rather than focusing solely on state-level goals and ambitions, this lens highlights the moral gravity of the climate crisis, pressing for urgent action to address the violence exerted among ourselves as human beings and to the environment on which we depend.